GnIH secreted by green light exposure, regulates bone mass through the activation of Gpr147 - Yu You; Konglin Huo; Liang He; Tongyue Wang; Lei Zhao; Rong Li; Xiaoqing Cheng; Xuebin Ma; Zhiying Yue; Stefan Siwko; Ning Wang; Lujian Liao; et al. (Bone Research)
Abstract Reproductive hormones associated with the hypothalamic-pituitary-gonadal (HPG) axis are closely linked to bone homeostasis. In this study, we demonstrate that Gonadotropin inhibitory hormone (GnIH, one of the key reproductive hormones upstream of the HPG axis) plays an indispensable role in regulating bone homeostasis and maintaining bone mass. We find that deficiency of GnIH or its receptor Gpr147 leads to a significant reduction in bone mineral density (BMD) in mice primarily by enhancement of osteoclast activation in vivo and in vitro. Mechanistically, GnIH/Gpr147 inhibits osteoclastogenesis by the PI3K/AKT, MAPK, NF-κB and Nfatc1 signaling pathways. Furthermore, GnIH treatment was able to alleviate bone loss in aging, ovariectomy (OVX) or LPS-induced mice. Moreover, the therapy using green light promotes the release of GnIH and rescues OVX-induced bone loss. In humans, serum GnIH increases and bone resorption markers decrease after green light exposure. Therefore, our study elucidates that GnIH plays an important role in maintaining bone homeostasis via modulating osteoclast differentiation and demonstrates the potential of GnIH therapy or green light therapy in preventing osteoporosis.